TRANSFORMASI TATANAN RUANG DAN BENTUK PADA INTERIOR TONGKONAN DI TANA TORAJA SULAWESI SELATAN - Stephany, Shandra (Dimensi Interior, 2009)
The traditional house of Toraja, Tongkonan, is a heritage house that has been passed down through generations of the Toraja clan. To own a Tongkokan is truly an honour to the Toraja people. Science, modern technology and social transitions have changed and improved the living standards of the society of Toraja in South Sulawesi. Since then, the Tongkonan has undergone transformations in its structure and form, from its traditional shape which was still under the influence of Aluk Todolo beliefs, to the more modern shape and function that have been adapted to the needs of the society. This aim of this research is to observe the transformations that have occurred on the Tongkonan. The results show that transformations have taken place on the space arrangement and functions because of the increase in the complexity of needs. Transformation of materials can also be found due to the decrease in the availability of raw materials. The development of technology as well as social, cultural, religious and economic transitions have been the main factors triggering Tongkonan transformations.